A study of two diuretic/potassium combinations in heart failure. Issue 711 (January 1985) - Hussain, M.; Walton, K.; Davidson, C.; Morgan, D. B.
Abstract : The effect of potassium supplements was studied in 28 patients taking long term frusemide (40-80 mg daily). Plasma potassium fell when supplements were stopped, and rose towards prior values on the potassium/frusemide combination, Diumide K. In a crossover study in 14 of these patients comparing equivalent doses of frusemide, Diumide K (frusemide 40 mg, potassium 8 mmol), bumetanide, and Burinex K (bumetanide 0.5 mg, potassium 7.7 mmol) plasma potassium was lower on frusemide than on bumetanide. On Diumide K and Burinex K plasma potassium rose significantly but did not reach the levels on prior therapy. Small doses of potassium in combined formulations seem to be effective in countering the mild hypokalaemia caused by loop diuretics.